Surveying the surveyors: Richard Thornton and his publishers. - Robson, Brian; Wyke, Terry (Northern History)
Richard Thornton produced two outstanding large-scale plans of Manchester as the pinnacle of his work as a map surveyor. Yet, like the vast majority of nineteenth-century surveyors, little is known about him. This reflects the fact that most private surveyors were held in very low esteem, although the quality of Thornton's work should have exempted him from any such scorn. His two plans, published in 1832 and 1851, are shown to be valuable and accurate depictions of the rapidly expanding town as it flourished as the groundbreaker of industrialization. Some new evidence about Thornton's life and work has been unearthed, yet even the most assiduous searches have produced relatively little to flesh out his skeletal details. What is clear, however, is that the impact of Thornton's two plans owes much to the respective support of Thomas Bancks - a local bookseller - and Joseph Adshead - estate agent, social campaigner and local politician - both of whom took the risk of publishing and promoting Thornton's surveys in the very uncertain market for commercial maps.